Neuropsychological Intervention in Brain Injuries in Childhood and Adolescence - da Silva Gusmão Cardoso, Thiago; de Freitas Feldberg, Silvia Cristina [UNESP]; de Mello, Claudia Berlim (Springer Nature, 2024)
The chapter addresses the importance of neuropsychological rehabilitation for children and adolescents with congenital or acquired brain injuries. The development of the central nervous system begins in the first weeks of pregnancy, and injuries caused by different clinical conditions can negatively affect the brain maturation process, resulting in motor, sensory, and cognitive impairments. Neuropsychological intervention plays a crucial role in these cases, helping to set realistic expectations for the patient’s performance and identifying areas with the greatest potential for developmental success. Exposure to enriched sensory environments and participation in early cognitive and psychosocial stimulation programs are known to improve cognitive function and quality of life in children with brain injury. To illustrate the rehabilitation process in pediatric patients with brain injury, the chapter presents a case study of an adolescent diagnosed with cerebral palsy. The neuropsychological intervention involved structured activities in group and individual sessions, specially designed to both enhance cognitive function through specific training and promote functionality in several areas of the adolescent’s life. The chapter aims to provide references and guidance to rehabilitation therapists working with children and adolescents with brain injuries, aiming at stimulating academic, cognitive, and social skills and improving quality of life.
Keywords: Adolescence; Brain injuries; Childhood; Cognitive function; Neuropsychological rehabilitation